Dedradasi Metilen Biru Secara Fotolisis Dengan Katalis Cdots Doping Au - Septian Budiman; Hary Sanjaya; Isnaeni Isnaeni; Umar Kalmar Nizar; Edi Nasra (Departemen Kimia FMIPA UNP, 2022)
The degradation of methylene blue was carried out by photolysis method with the help of a Cdots/Au catalyst. This study aims to determine the optimum concentration of dopen Au for Cdots and the optimum time for degradation of methylene blue with the help of a Cdots/Au catalyst. The photolysis method was carried out in a reactor equipped with 3 15 watt lamps with a UV wavelength of 254 nm. The absorption of methylene blue was measured using a spectrophotometer UV-Vis. The optimum Au dopen results were obtained at a concentration of 25 ppm with a degradation percentage of 39.94% and the optimum time for photolysis degradation was 6 hours of irradiation with a degradation percentage of 70.28%.